(untitled) (Eurasian Medical Research Periodical, 2023)
The current guidelines for eliminating Helicobacter pylori (H. pylori) in adults vary from those for children. infected with H. pylori should always seek treatment to eliminate the infection. as a result of the possibility of contracting infections outside of the digestive system. Instead of focusing just on H. pylori infection, we should evaluate all potential reasons before treating affected infants. In fact, the test-and-treat approach is not recommended for kids according to worldwide pediatric standards. Therefore, in order to properly analyse all of the potential causes of the symptomatology and to enhance the eradication rate, gastroscopy with antimicrobial susceptibility testing by culture on stomach biopsies should be conducted before to beginning the eradication therapy in children. If antibiotic susceptibility testing is unavailable, gastroscopy is nevertheless advised in order to determine the true source of any symptoms rather than only looking for H. pylori. Because there aren’t as many antibiotics available for kids as there are for adults, doctors sometimes resort to antimicrobial susceptibility testing to cut down on treatment failures. Amoxicillin, clarithromycin, and metronidazole, in various combinations, are the principal antibiotics prescribed for children. When treating an infection without first determining its antimicrobial susceptibility, it is common practice to use a 14-day course of triple therapy. In cases of double-resistance or as a secondary therapeutic option, triple therapy with a high dose of amoxicillin is an option worth considering. From there, we might choose quadruple treatment with or without bismuth salts, which is based on therapeutic regimens typically administered to adults. Unfortunately, many children are less compliant with treatment regimens because of the severe side effects they may experience. This analysis also takes a look at several alternatives to standard pediatric care that are gaining popularity